-(8Y+4)-(-7-8)=-4

Simple and best practice solution for -(8Y+4)-(-7-8)=-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(8Y+4)-(-7-8)=-4 equation:


Simplifying
-1(8Y + 4) + -1(-7 + -8) = -4

Reorder the terms:
-1(4 + 8Y) + -1(-7 + -8) = -4
(4 * -1 + 8Y * -1) + -1(-7 + -8) = -4
(-4 + -8Y) + -1(-7 + -8) = -4

Combine like terms: -7 + -8 = -15
-4 + -8Y + -1(-15) = -4

Multiply -1 * -15
-4 + -8Y + 15 = -4

Reorder the terms:
-4 + 15 + -8Y = -4

Combine like terms: -4 + 15 = 11
11 + -8Y = -4

Solving
11 + -8Y = -4

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Add '-11' to each side of the equation.
11 + -11 + -8Y = -4 + -11

Combine like terms: 11 + -11 = 0
0 + -8Y = -4 + -11
-8Y = -4 + -11

Combine like terms: -4 + -11 = -15
-8Y = -15

Divide each side by '-8'.
Y = 1.875

Simplifying
Y = 1.875

See similar equations:

| 5p-8p=0 | | 3(2x-6)=2(x+6) | | 4(-2x+5)=-12 | | 0.45(12)+0.06X=0.18(6+X) | | 4r+8=-28 | | 8/5.5=94/x | | f(80)=x(40-x) | | x^2-5=-31 | | X/11=-8 | | =8(a+4) | | 2s+16=-25 | | 6y+3=10 | | 5s+7=12 | | 3.2-y=7.5 | | 18x^2+18y^2-54x-72y-36=0 | | log(base)2(x^2+6x-64)-log(base)2(x-5)=3 | | 30-7b=(16+8b)4 | | 5c+6=7c-4 | | 3x+16-8x=-4(2x-4) | | -3=h/5 | | 2a-16=(8+2a)12 | | x-20=x+x+80 | | z=2x^2-8xy-2y^2 | | 12(1280+100)= | | 24-8v=6u | | .4(3x+6)=1.6-(x+2) | | 18+11r=9r | | 36x=275000 | | X/4?4=3•4 | | a-9=(13+3a)3 | | 5(3x-2)=7x-2 | | (t)+(t+1)+(t+3)= |

Equations solver categories